Credit Expansion and Its Impact on Income Inequality of the Provinces in Indonesia - Anhar Fauzan Priyono; Pipit Pitriyan; Heriyaldi Heriyaldi; Indra Maipita (Jurnal Economia, 2019)
AbstractThis research aims to study the determinants of income inequality at the provincial level in Indonesia, through observing MSMEs credit, government expenditure of education and health, school participation rate, and unemployment rate. We employed Fixed effect panel data, implementing Panel Corrected Standard Error (PCSE) and found that MSMEs credit, government expenditure on education, and school participation rate are significant in reducing income inequality. On the other hand, unemployment has been proven to have a positive impact on income inequality. However, implementation of National Health Insurance, relative to our period of observation, makes the result of government expenditure on health requires further analysis. Empirical result found that the increase in credit distribution to the MSME sector can reduce the level of income inequality and highest to lowest income ratio, on average in each province in Indonesia. The government is expected to focus on education and health budget to improve the community's quality of life.  Keywords: Gini Index, Government Expenditure, Highest to Lowest Income Ratio, MSMEs credit expansion, Panel dataEkspansi Kredit dan Dampaknya terhadap Ketimpangan Pendapatan pada Provinsi di IndonesiaAbstrakPenelitian ini bertujuan untuk mempelajari faktor-faktor yang memengaruhi ketimpangan pendapatan di tingkat provinsi di Indonesia, dengan mengamati kredit UMKM, pengeluaran pemerintah untuk pendidikan dan kesehatan, tingkat partisipasi sekolah, dan tingkat pengangguran. Dengan memanfaatkan pendekatan Fixed Effect dengan Panel Corrected Standard Error (PCSE), ditemukan bahwa kredit UMKM, pengeluaran pemerintah untuk pendidikan, dan tingkat partisipasi sekolah secara signifikan mampu mengurangi ketimpangan pendapatan. Di sisi lain, pengangguran terbukti memiliki dampak positif pada ketimpangan pendapatan. Namun, penerapan Jaminan Kesehatan Nasional, relatif terhadap periode pengamatan kami, membuat hasil pengeluaran pemerintah untuk kesehatan memerlukan analisis lebih lanjut. Di lain pihak, ditemukan bahwa peningkatan distribusi kredit ke sektor UMKM dapat mengurangi tingkat ketimpangan pendapatan dan rasio pendapatan tertinggi hingga terendah, rata-rata di setiap provinsi di Indonesia. Pemerintah diharapkan fokus pada anggaran pendidikan dan kesehatan untuk meningkatkan kualitas hidup masyarakat. Kata Kunci: indeks Gini, pengeluaran pemerintah, highest to lowest income ratio, UMKM, ekspansi kredit